Efektifitas akupresur terhadap dismenore Pada remaja putri - -, Julianti -; Hasanah, Oswati -; -, Erwin - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Acupressure is nonpharmacologic therapy for dysmenorrhea. The purpose of  this research was to identify the effect of acupressure on pain (intensity and quality) in adolescent with dysmenorrhea at SMK Muhammadiyah 2 Pekanbaru. This study was quasi-experimental with  non-equivalent pretest-posttest kontrol group design. The sample were 52 respondens, devided into intervention and control group with purposive sampling method. Acupressure reduce pain intensity and quality signicantly p-value (< α 0,05). Dismenorrhea can decrease as 0,615 point for the pain intensity and pain quality as 0,577 point. The research recommended that acupressure at LI4 (Hequ) and PC6 (Neiguan) is effective as self theraphy in aldolescent and can be use widely as part of nursing intervention. Key words : Acupressure, pain of intensity,  pain of quality